1984
DOI: 10.1093/ajcp/81.5.629
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the MS-2® and Lumac® Systems for the Rapid Screening of Urine Specimens

Abstract: The authors have evaluated the MS-2 (Abbott) and Lumac (3M) systems for the rapid screening of urine specimens for bacteriuria. These systems, which can detect significant levels of microorganisms in urine in five hours (MS-2) or 30 minutes (Lumac), were compared with a standard overnight plate culture method. Three hundred fifty-eight voided urine specimens were examined. The two systems compared equally at greater than 10(5) colony-forming units (CFU)/mL in terms of false-positive results (11%), false-negati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1985
1985
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…In contrast, organisms with a thicker cell wall, including the mycobacteria and Candida , exhibited increasing signal over time due to the additional time required to break down the cell walls to release ATP (Figure 2). The increase in signal is a distinguishing feature of mycobacteria and Candida that could allow differentiation from other common organisms associated with bacteriuria, namely, E. coli and mixed Gram-positive cocci [26]. It was also routinely observed that MTB had a modest increase in signal relative to other mycobacteria.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In contrast, organisms with a thicker cell wall, including the mycobacteria and Candida , exhibited increasing signal over time due to the additional time required to break down the cell walls to release ATP (Figure 2). The increase in signal is a distinguishing feature of mycobacteria and Candida that could allow differentiation from other common organisms associated with bacteriuria, namely, E. coli and mixed Gram-positive cocci [26]. It was also routinely observed that MTB had a modest increase in signal relative to other mycobacteria.…”
Section: Resultsmentioning
confidence: 99%
“…This is much higher than the approximately 20% sensitivity typical of sputum smear microscopy in HIV-positive patients with suspected TB [26] and is on a par with alternative diagnostic tests like the LAM ELISA, which has a reported sensitivity of 67–85% in HIV-positive patients [5]. All 19 flagged samples exhibited an increase in S : N for at least one time point after T1, and all yielded an average S : N/T1 of 0.98 or greater.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations